DESIGN OF THE ANALYTIC HIERARCHY PROCESS (AHP) METHODS IN COMPETITIVE DEVELOPMENT STRATEGY OF HIGHER EDUCATION BASED ON INFORMATION TECHNOLOGY - -, Yulmaini; Sanusi, Anuar; Yusendra, M.Ariza Eka; Mutiara, Suci (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Higher education has a very strategic role in the midst of society. The strategic role is often formulated into three paradigms, namely teaching universities, research universities, and bastion of civilization. Strategic concepts towards a quality college will ideally occur if the Tridarma of Higher Education is increased supported by an information technology system, entrepreneurship, and reliable human resources (Sanusi, et al. 2016). The purpose of the strategy of developing competitiveness of information technology based on information technology is to determine criteria that have contributed to information technology and internal management. This reasearch is used AHP method with the number of respondents is 67 respondents. Criteria in this research are internal management & organization (sub criteria : staff performance, planning system, budget allocation, operating prochecure exellence, tranparant management system), academic athmosphere (academic society relationship, The quality of educational processes, Transparency & accountability in academic life, Motivation to work in all academic activities, Community invomen in academic & teaching-learning), and university competitive sustainability (Innovations, Networks, Reputation, Relevance, dan Commercialization). This research produced the biggest criteria weight was academic atmosphere. Information technology has a contribution to internal management of 63.2%, while internal management has a large contribution to the academic atmosphere of 79.8%.Keywords: competitiveness, information technology, AHP, universities